Quantitative studies of the interactions of metalloproteins with gold nanoparticles identification of dominant properties of the protein that underlies the spectral changes - Lunt, Elizabeth A M (Langmuir : the ACS journal of surfaces and colloids, 2009)
The interaction of cytochrome C and a number of its components such as the apo protein, heme and a coordinated iron with gold nanospheres, has been investigated. The role of the heme group and its effect on the observed spectroscopic properties following binding of cytochrome C to the gold surface has been evaluated. Binding of the heme group directly to the gold is not observed, but the presence of the heme group and its effect on the interaction with the metal surface is shown to be influential. Other factors such as the metal oxidation state and the metal-free heme are also studied. A comparison to serum albumin binding as a nonmetallic protein provides further insight into the interaction characteristics